2019
DOI: 10.18061/emr.v13i1-2.6012
|View full text |Cite
|
Sign up to set email alerts
|

Two Studies of Autonomous Sensory Meridian Response (ASMR): The Relationship between ASMR and Music-Induced Frisson

Abstract: In recent years, a widely popular phenomenon has emerged as exemplified in thousands of videos available on the Internet. Referred to using the impressive sounding term "Autonomous Sensory Meridian Response" (abbreviated ASMR), followers claim that ASMR videos evoke a special "tingling" sensation that is regarded as highly pleasurable and relaxing. The popularity of this phenomenon is reflected in individual ASMR videos receiving more than 43 million views and a reddit ASMR forum with over 130,000 subscribers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 26 publications
4
52
0
Order By: Relevance
“…[1][2][3][4][5] Although there are many ASMR-inducing videos on the internet (some with millions of views), there is limited scientific understanding of the phenomenon. [1][2][3][4][5] Two surveys found that among the most common triggers were whispering, "crisp sounds", people speaking softly, and soft touching of hair or face. [1,4] The cardinal feature of ASMR videos is an auditory stimulus, often recorded in stereo.…”
Section: What Is Known About Asmr?mentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5] Although there are many ASMR-inducing videos on the internet (some with millions of views), there is limited scientific understanding of the phenomenon. [1][2][3][4][5] Two surveys found that among the most common triggers were whispering, "crisp sounds", people speaking softly, and soft touching of hair or face. [1,4] The cardinal feature of ASMR videos is an auditory stimulus, often recorded in stereo.…”
Section: What Is Known About Asmr?mentioning
confidence: 99%
“…In ASMR certain "trigger" stimuli evoke feelings of calm and relaxation, together with a pleasant tingling sensation that typically starts in the scalp, head and shoulders and spreads down the spine and into the limbs. [1][2][3][4][5] Although there are many ASMR-inducing videos on the internet (some with millions of views), there is limited scientific understanding of the phenomenon. [1][2][3][4][5] Two surveys found that among the most common triggers were whispering, "crisp sounds", people speaking softly, and soft touching of hair or face.…”
Section: What Is Known About Asmr?mentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in brightness may reflect similar auditory looming mechanisms: As lower frequency sound waves are absorbed less and generally travel further than those at higher frequencies, increasing ramps of higher frequency energy may act as a spectral analogy for auditory looming and decreased proximity between listener and event. Notably, Kovacevich and Huron (2018) recently proposed a vigilance account of the related autonomous sensory meridian response (ASMR) phenomenon (Barrett & Davis, 2015), often elicited by whispering sounds that imply proximity and are characterized by high brightness. However, this appears less intuitive than the link between auditory looming and loudness, and brightness has yet to receive empirical support in broader auditory looming research; an alternative possibility is that the existing correlations between chills and brightness are mediated by different, underlying psychological mechanisms.…”
Section: Vigilance Theory Of Musical Chillsmentioning
confidence: 99%